Estudio de tiempos y movimientos para la optimización de la producción en el área de poscosecha de la Florícola Rosas del Cotopaxi - Naranjo Veloz, Christian Fabian (2022)
The study of times and movements was carried out in the Floriculture Company "Rosas del Cotopaxi", located in the parish Tanicuchi of Latacunga Canton, province of Cotopaxi. The research was based on a methodological study focused on the organization of work including the Methods Engineering with the application of the study of times and movements. The main objective of the research work is to increase productivity in the post-harvest area of the flower farm "Rosas del Cotopaxi" by optimizing times and movements, reducing unnecessary activities in the post-harvest process. First of all, bibliographic information was compiled, which is necessary to support theoretical and scientific bases concerning Method Engineering and the study of time and movements. Subsequently, the current situation of the Floriculture Plant was inspected through the use of Process Diagrams, which made it possible to represent each of the activities carried out in the post-harvest area, as follows: reception of roses, leaf removal, classification, bonking, stem cutting, quality control, and packing. The aforementioned activities were used to record the times of each one of them. The initial diagnosis of the company was taken as a basis, where a total of 946.95 bonches (25 stems*bonche) were produced per month. Improvements were made in new work methods with the combination of activities, achieving a decrease in cycle time from 10.14 min per bonche to 8.29 min per bonche, resulting in an increase in the monthly production capacity of 1158.20 bonches (25 stems*bonche) and increasing productivity by 22%, which is the main objective of this work.